Central Giant Cell Granuloma: A Potential Endodontic Misdiagnosis - Seifi, Safoura; Fouroghi, Ramin (Iranian Endodontic Journal, 2010)
Central Giant Cell Granulomas (CGCGs) may manifest as radiolucencies anywhere in the mandible or maxilla. In rare cases, it can appear as a localized periradicular area and mimic an endodontic lesion. This case report presents an uncommon location of CGCG which was not accurately diagnosed nor timely treated. Periodic follow ups of periapical radiolucencies after RCT are necessary. Dentists should include CGCG in differential diagnosis of lesions that are refractory to endodontic treatment. [Iranian Endodontic Journal 2009;4(4):158-60]